REAKSI PENATAAN ULANG FRIES PADA EUGENIL ASETAT - kusmiyati, kusmiyati; Matsjeh, Sabirin; Jumina, Jumina (Pharmaciana, 2011)
Fries Rearrangement of eugenyl acetate in order to study allilic substituentgroup influence has been done. Fries rearrangement of eugenyl acetate was done byheating at 120Â°C for 3 hours under AlCl3, dichloromethane as the catalyst and solvent,respectively. The structure of the compound was identified using Infra Redspectrometry (IR) and GC-MS. The result of te research showed that rearrangementfries of eugenyl acetate are not formed, but yielded lightly brown oil of dimmer.